Pre- and Postsynaptic Activation of GABAB Receptors Modulates Principal Cell Excitation in the Piriform Cortex - Gerrard, Leah B.; Tantirigama, Malinda L. S.; Bekkers, John M. (Frontiers in Cellular Neuroscience, 2018)
The piriform cortex (PC), like other cortical regions, normally operates in a state of dynamic equilibrium between excitation and inhibition. Here we examined the roles played by pre- and postsynaptic GABAB receptors in maintaining this equilibrium in the PC. Using whole-cell recordings in brain slices from the anterior PC of mice, we found that synaptic activation of postsynaptic GABAB receptors hyperpolarized the two major classes of layer 2 principal neurons and reduced the intrinsic electrical excitability of these neurons. Presynaptic GABAB receptors are expressed on the terminals of associational (intracortical) glutamatergic axons in the PC. Heterosynaptic activation of these receptors reduced excitatory associational inputs onto principal cells. Presynaptic GABAB receptors are also expressed on the axons of GABAergic interneurons in the PC, and blockade of these autoreceptors enhanced inhibitory inputs onto principal cells. Hence, presynaptic GABAB autoreceptors produce disinhibition of principal cells. To study the functional consequences of GABAB activation in vivo, we used 2-photon calcium imaging to simultaneously monitor the activity of ~200 layer 2 neurons. Superfusion of the GABAB agonist baclofen reduced spontaneous random firing but also promoted synchronous epileptiform activity. These findings suggest that, while GABAB activation can dampen excitability by engaging pre- and postsynaptic GABAB heteroreceptors on glutamatergic neurons, it can also promote excitability by disinhibiting principal cells by activating presynaptic GABAB autoreceptors on interneurons. Thus, depending on the dynamic balance of hetero- and autoinhibition, GABAB receptors can function as variable modulators of circuit excitability in the PC.